Osteonecrosis of the Femoral Head: Can Arthroplasty be Avoided—A Brief Review of Common Interventions - Einhorn, Thomas A.; Anoushiravani, Afshin A.; Chen, Kevin K.; Draper, Thomas; Tsismenakis, Tony; Iorio, Richard (The Journal of Hip Surgery, 2019)
Osteonecrosis of the femoral head (ONFH) is a rapidly progressive degenerative disease frequently affecting individuals within their fourth and fifth decade of life. Though often asymptomatic, patients with ONFH may present with a wide range of symptoms, including deep groin pain. There are many classification systems used to stratify disease severity, of which the Association of Research Circulation Osseous (ARCO) classification system is currently the most comprehensive. Once diagnosed, an estimated 75% of patients will experience femoral head collapse within three years of diagnosis if left untreated. Currently, the only definitive intervention available for ONFH is total hip arthroplasty (THA). However, recent advancements have been made with respect to the available treatment modalities. In this article, the author review the management of ONFH, providing clinicians with the necessary information to counsel their patients.
Keywords: osteonecrosis of the femoral head; bone marrow aspirate concentrate; stem cells; core decompression; bisphosphonates; hyperbaric oxygen therapy; shockwave therapy; vascularized fibular grafts; vascularized iliac grafts